The Development of Learning Media of 2-Stroke Engine Manufactured by 3D Print for Distance Learning - Moch Solikin; Aan Yudianto; I Wayan Adiyasa (Faculty of Engineering, Universitas Negeri Yogyakarta, 2022)
The Covid19 pandemic that has hit the world requires educational media innovations that are portable, lightweight, and easy to operate for online learning purposes. This study aims to develop learning media for students of the Light Vehicle Engineering Vocational School on the topic of a 2 stroke engine using a engine model made using 3D printing technology with Polylactic Acid as the base material. This is carried out to develop media to support teachers of related subjects in the implementation of online learning. This study uses the Design and Development (DD Research) method which consists of identifying the problem, describing the objectives, design and development, testing, evaluating and finally communicating the results. Data analysis was carried out quantitatively and qualitatively to explain the obtained results. The checklist evaluation was performed to assess the produced learning media. The results indicated that the utilization of 3D print to create lightweight, portable and representable learning media has been successfully achieved. The constructed learning media is aimed to be utilized to explain the competency of two-strokes engine in a distance learning.